POTENSI LONGSOR BERDASARKAN ANALISIS KINEMATIK PADA AREA LOW WALL PT. BUKIT ASAM TBK, SITE TANJUNG ENIM, SUMATERA SELATAN - Siti Khodijah; Utari Sonya Monica; Jodistriawan Ersyari; Nur Khoirullah; Raden Irvan Sophian (Jurnal Teknologi Mineral dan Batubara, 2023)
PT. Bukit Asam Tbk is an open-pit coal mining company in Muara Enim, Soutgh Sumatra. In open-pit mining activities, slope stability analysis is carried out to evaluate the mine in order to create a safe mining process. Several types of slope failure are associated with geological structures. This research was conducted to identify the type of landslides in the low wall area of Pit X PT. Bukit Asam Tbk and determine the slope stability factor based on discontinuity data using the scanline method at 8 observation points that represent the lithology of the low wall area. Methods used in this research is kinematic analysis, slope stability analysis on plane slide types and wedge. Based on the kinematic analysis, it was identified that the Pit X low wall area has the potential for plane and wedge type landslides with a relatively stable slopes.